FAKTOR DETERMINAN YANG MEMPENGARUHI MINAT BERWIRAUSAHA MAHASISWA DENGAN MENGGUNAKAN PENDEKATAN SEE - Sugiharti, Sugiharti (STIE Totalwin Semarang, 2014)
The purpose of this study was to analyze the magnitude of the influence of perceived feasibility, perceived desirability, and propensity to act to entrepreneurial intention. The data in this study were obtained from student at STIE Totalwin Semarang. Results and the theoretical implications of this research is that this study supports previous research that says that the perceived feasibility, perceived desirability, and propensity to act affect to entrepreneurial intention.